Aggregation of Asian-American subgroups masks meaningful differences in health and health risks among Asian ethnicities: an electronic health record based cohort study - Nancy P. Gordon; Teresa Y. Lin; Jyoti Rau; Joan C. Lo (BMC, 2019)
Abstract Background Few large cohort studies have examined the prevalence of diabetes mellitus (DM), hypertension (HTN), coronary artery disease (CAD), obesity, and smoking among middle-aged and older adults in the major Asian-American ethnic groups and Native Hawaiian/Pacific Islanders (PIs). The aim of this study was to evaluate how prevalence of these conditions and risk factors differs across Asian-American and PI ethnic groups and compares with an aggregated All Asian-American racial group. Methods This study used a cohort of 1.4 million adults aged 45 to 84 who were Kaiser Permanente Northern California health plan members during 2016. The cohort included approximately 274,910 Asian-Americans (Chinese, Filipino, Japanese, Korean, Southeast Asian, South Asian, other), 8450 PIs, 795,080 non-Hispanic whites, 107,200 blacks, and 210,050 Latinos. We used electronic health record data to produce age-standardized prevalence estimates of DM, HTN, CAD, obesity (using standard and Asian thresholds), and smoking for men and women in all racial/ethnic subgroups and compared these subgroups to an aggregated All Asian-American racial group and to whites, blacks, and Latinos. Results We found large differences in health burden across Asian-American ethnic subgroups. For both sexes, there were 16 and > 22 percentage point differences between the lowest and highest prevalence of DM and HTN, respectively. Obesity prevalence among Asian subgroups (based on an Asian BMI ≥ 27.5 kg/m2 threshold) ranged from 14 to 39% among women and 21 to 45% among men. Prevalence of smoking ranged from 1 to 4% among women and 5 to 14% among men. Across all conditions and risk factors, prevalence estimates for Asian-American and PI ethnic groups significantly differed from those for the All Asian-American group. In general, Filipinos and PIs had greater health burden than All Asians, with prevalence estimates approaching those of blacks. Conclusions In a population of middle-aged and older adult Northern California health plan members, we found substantive differences in prevalence of chronic cardiovascular conditions, obesity, and smoking across Asian-American ethnic groups and between Asian-American ethnic groups and an aggregated All Asian racial group. Our study confirms that reporting statistics for an aggregated Asian-American racial group masks meaningful differences in Asian-American ethnic group health.